Psychological Distress and Access to Mental Health Services Among Undergraduate Students During the COVID-19 Lockdown in Uganda - Nantaayi, Brandy; Ndawula, Rodney Kato; Musoke, Phillip; Ssewante, Nelson; Nakyagaba, Lourita; Wamala, Joyce Nakiganda; Makai, Emmanuel Arthur; Wannyana, Babrah; Wamala, Nicholas Kisaakye; Kanyike, Andrew Marvin; Akech, Gabriel Madut; Ojilong, Daniel; et al. (Frontiers in Psychiatry, 2022)
Background: Lockdown is an important public health approach aimed at curbing the raging effect of the coronavirus disease – 2019 (COVID-19). This study aimed at determining the impact of prolonged lockdown on mental health and access to mental health services among undergraduate students in Uganda. Methods: An online cross-sectional study was conducted anonymously among undergraduates across 10 universities in Uganda. The Distress Questionnaire-5 (DQ-5) and the Patient Health Questionnaire-2 (PHQ-2) were used. Logistic regression analysis was conducted to determine factors associated with psychological distress. Results: We enrolled 366 participants with a mean age of 24.5± 4.6 years. The prevalence of psychological distress was 40.2% (n=147) (cut off 14/25 based on DQ-5) while depression stood at 25.7% (n=94) (cut off 3/6 based on PHQ-2) with mean scores of 12.1± 4.6 and 1.7± 1.6 respectively. Female gender (aOR: 1.6, 95%CI: 1.0-2.6, p=0.032), pursuing a non-medical program (aOR: 2.2, 95%CI: 1.3-3.7, p=0.005) were factors associated with psychological distress while non-medical program (aOR: 2.2, 95%CI: 1.3-3.7, p=0.005) was associated with increased depression. Access to mental health services was associated with both reduced distress (aOR: 0.5, 95%CI: 0.3-0.8, p=0.005) and depression (aOR: 0.6, 95%CI: 0.3-0.9, p=0.034). A majority (65.3%) of the participants reported knowing how to access mental health care and 188(51.4%) reported having needed emotional support but, only 67(18.3%) ever sought care from a mental health professional. Of those who had access, only 10 (7%), and 13 (9%) accessed a counselor or a mental health unit, respectively. The barriers to accessibility of mental health care included financial limitations (49.5%), lack of awareness (32.5%), lack of mental health professionals (28.4%), and stigma (13.9%). Conclusion: Among university students in Uganda during the COVID- 19 lockdown, the burden of psychological distress and depression was substantial. However, access to mental health services was limited by several factors.